PENGARUH VARIASI pH LARUTAN DEKOLORISASI ASAM ALKOHOL TERHADAP KUALITAS PEWARNAAN BASIL TAHAN ASAM (BTA) METODE ZIEHL NEELSEN - Ardy Prian Nirwana; Tazkiyatul Amaliyah (Klinikal Sains : Jurnal Analis Kesehatan, 2026)
Tuberculosis (TB) is one of the infectious diseases with a high mortality rate worldwide, including in Indonesia. Acid-Fast Bacilli (AFB) microscopic examination using the Ziehl-Neelsen method remains a widely used diagnostic method for TB. One of the crucial stages in Ziehl-Neelsen staining is the decolorization process using an acid-alcohol solution. Variations in the pH of the decolorizing solution are suspected to affect the quality of AFB staining results. This study aimed to determine the effect of acid-alcohol pH variations on the quality of AFB staining using the Ziehl-Neelsen method. The study utilized a laboratory experimental analytical design with acid-alcohol pH variations of 0.5, 1.0, 2.0, and 3.0. The research sample consisted of 24 smears, which were observed based on the microscopic quality of the AFB staining results. Data were analyzed using the Kruskal-Wallis test, followed by a post hoc pairwise comparison test using the Bonferroni correction. The Kruskal-Wallis test results showed a significant effect of acid-alcohol pH variation on the quality of AFB staining (p < 0.05). Post hoc test results indicated significant differences between pH 0.5 and pH 2.0 (p = 0.038), pH 0.5 and pH 1.0 (p < 0.001), as well as pH 3.0 and pH 1.0 (p = 0.013). The pH 1.0 group had the highest mean rank of 21.50, indicating the best staining quality in accordance with the AFB examination quality standards set by the Ministry of Health of the Republic of Indonesia. Therefore, variations in acid-alcohol pH affect the quality of Ziehl-Neelsen AFB staining, and pH 1.0 is recommended as the optimal pH for the decolorizing solution